The effect of the waiting room's environment on level of anxiety experienced by children prior to dental treatment: a case control study - Avia Fux-Noy; Maayan Zohar; Karin Herzog; Aviv Shmueli; Elinor Halperson; Moti Moskovitz; Diana Ram (BMC, 2019)
Abstract Background In addition to visit purpose, one of the environmental factors that can cause anxiety prior to dental treatment includes the waiting room experience, specifically the amount of time spent awaiting treatment and the waiting room environment. The purpose of this study was to compare the effect of the waiting room's environment on the level of anxiety experienced by children in multisensory and traditional waiting rooms. Methods Case control study. Test group waited for treatment in a multisensory waiting room, which consisted of a lighting column that children could touch and climb; as well as, rhythmic music played on loudspeakers. Control group waited for treatment in a traditional waiting room. Study participants were asked to answer the "Venham Picture Test", a dental anxiety scale, while in the waiting room prior to entering the treatment room. Chi-squared, Fisher's Exact tests, and linear regression were utilized. A p-value less than 0.05 was considered statistically significant. Results No significant difference in dental anxiety scores was found between the test and control groups according to waiting room type (p > .05). Dental anxiety was significantly higher in patients who had longer waiting time prior to treatment (p = 0.019). In addition, dental anxiety was significantly associated with visit purpose (p < .001): children waiting for dental examination or those scheduled for dental treatment with conscious sedation were less anxious than children waiting for emergency treatment. Conclusions A sensory adapted waiting room environment may be less important in reducing children's anxiety prior to dental treatment. Children's dental anxiety can be reduced by preventing emergency treatments, scheduling routine dental visits and decreasing waiting time. Trial registration TRN NCT03197129, date of registration June 20, 2017.